PENILAIAN KINERJA BERBASIS KELAS: SATU PENILAIAN - Fadly Azhar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This study aimed to evaluate the implementation of Classroom-BasedAssessment (CBA) among teachers of State Junior High Schools in Riau Province,Indonesia. The sample consisted of 297 English teachers. This study used the CIPPEvaluation Model focusing on the evaluation of these aspects: input, process and product.Questionnaires were administered in the collection of data for the aspects of input andprocess; while a checklist was used for the aspect of product. Findings for input showedthat the training and attitudes towards CBA is at a high level; while the aspects ofimplementation of knowledge and skills in CBA is at a moderate level. In the aspect ofprocess, it was found that the frequency of implementation of the types of CBA ismoderate; while the aspects of CBA in inviting experts and identifying honesty in a largegroup of students were a major constraint faced by teachers in implementing CBA. In theaspect of product, it was found that the majority of teachers tend to use the same rubrics asare found in the curriculum. The results showed that there was no significant difference inthe level of knowledge, attitudes and skills of teachers to conduct CBA based on theirschool location and school teaching experience. Overall, the sub-aspects of knowledge,attitudes and skills contribute 41.2 percent of the variable performance-based assessmentgrades, while 58.8 percent were attributed to other factors that are not taken into account inthis study. The implication of this study is that in order to implement CBA as adeterminant of approval, the proposed school needs to implement a planned and systematicongoing training, whether working with various parties, inviting experts in the CBAseminar in schools or sending teachers to attend seminars, courses and workshops in CBA.This study has implications for the existing evaluation system in Indonesian schoolsbecause the majority of experts and teachers tend to conclude CBA as a morecomprehensive evaluation system.Keywords: Classroom-based assessment, portfolio, input, process, and product